2003
DOI: 10.1021/es020955c
|View full text |Cite
|
Sign up to set email alerts
|

Human Donor Liver and Serum Concentrations of Perfluorooctanesulfonate and Other Perfluorochemicals

Abstract: Perfluorooctanesulfonate (PFOS, CaF17SO3-) has been identified in the serum of nonoccupationally exposed humans and in serum and liver tissue in wildlife. The purpose of this investigation was to determine whether PFOS liver concentrations in humans are comparable to the approximate 30 ng/mL average serum concentrations reported in nonoccupationally exposed subjects. Thirty-one donors (16 male and 15 female, age range 5-74) provided serum and/or liver samples for analysis of PFOS and three other fluorochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
147
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(153 citation statements)
references
References 12 publications
5
147
0
1
Order By: Relevance
“…The findings from this analysis of serum PFOS concentrations in 645 adult blood donors are consistent with previous, albeit sparse, human data (3M Company 2003; Hansen et al 2001;Olsen et al 2003b Hansen et al 2001). These findings were also comparable to a limited number of serum samples from Europe that were determined to have mean serum PFOS concentrations at 17 ppb in five pooled samples from a blood bank in Belgium, 53 ppb in six pooled samples from the Netherlands, and 37 ppb from six pooled blood samples from Germany (3M Company, 2003).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The findings from this analysis of serum PFOS concentrations in 645 adult blood donors are consistent with previous, albeit sparse, human data (3M Company 2003; Hansen et al 2001;Olsen et al 2003b Hansen et al 2001). These findings were also comparable to a limited number of serum samples from Europe that were determined to have mean serum PFOS concentrations at 17 ppb in five pooled samples from a blood bank in Belgium, 53 ppb in six pooled samples from the Netherlands, and 37 ppb from six pooled blood samples from Germany (3M Company, 2003).…”
Section: Discussionsupporting
confidence: 90%
“…PFOS has been detected at low parts per billion (nanogram per milliliter) concentrations in the general population (3M Company 2003;Hansen et al 2001;Olsen et al 2003b), although the scope and sample size of these investigations have been limited. Serum PFOS concentrations among production employees working in POSF-related processes have averaged between 0.5 and 2 ppm depending on work activity (range < 0.1-12 ppm) (Olsen et al 1999(Olsen et al , 2003a(Olsen et al , 2003c.…”
Section: Research | Articlementioning
confidence: 99%
“…They reported that PFOS concentrations in blood were lower than those in liver. [18][19][20] Already in 1979 studies in rats showed that PFOS is well absorbed orally and accumulates primarily in the liver and, to a lesser extent, in the serum or plasma. [21] In contrast, some studies resulted in highest values in blood and lower values in liver.…”
Section: Analytical Challengesmentioning
confidence: 99%
“…[60] As expected, the PFOS burden in human liver was higher than in human blood. For PFOS the mean liver to serum ratio was 1.3 : 1 calculated from PFC analyses of liver and serum samples of 23 male and female US donors, [20] whereas the liver to serum ratio was 3.5 : 1 for 12 Spanish human tissue samples. [61] PFC pattern in human tissues PFOS, PFOA, PFHxS and PFOSA were detected most frequently in serum samples of the US population.…”
Section: Levels and Trends In Humansmentioning
confidence: 99%
“…In recent years, PFCs especially perfluorooctanoic acid (PFOA) and perfluorooctanyl sulfonate (PFOS) have received much attention because they were ubiquitously detected in various environmental media [3][4][5][6][7][8][9][10][11] and in the body of wildlife [12,13] and human beings [14][15][16][17]. Though their sources, fate and transport in the environment are not well understood, it has been known that they are directly released into the environment or indirectly formed [18].…”
Section: Introductionmentioning
confidence: 99%